Radiographic measurements of hip dysplasia at skeletal maturity—new reference intervals based on 2,038 19-year-old Norwegians - Laborie, Lene Bjerke; Engesæter, Ingvild Øvstebø; Lehmann, Trude Gundersen; Sera, Francesco; Dezateux, Carol; Engesæter, Lars Birger; Rosendahl, Karen (Skeletal radiology, 2013)
Objective Normative references for radiographic measurements commonly used in the diagnosis of developmental dysplasia of the hip at skeletal maturity are incomplete. The present study therefore aimed to establish new gender-specific standards for measurements reflecting the acetabular morphology, namely Sharp’s angle, the acetabular roof angle of Tönnis (AA) and the acetabular depth-width ratio (ADR), and measurements reflecting the position of the femoral head related to the acetabulum, namely the center-edge (CE) angle of Wiberg, the refined CE angle of Ogata, and the femoral head extrusion index (FHEI). The joint space width (JSW) is also reported. Materials and methods The population-based 1989 Bergen Birth Cohort ( n = 3,935) was invited at age 19 years to a follow-up during 2007–09, of which 2,038 (52 %) attended. A standardized antero-posterior radiograph was assessed. The normative references are presented as mean ± standard deviation (SD) and 2.5–97.5 percentiles with 95 % confidence intervals. Results A total of 2,011 (841 males, 1,170 females, mean age 18.6 (SD 0.6)) radiographs were analyzed. Sharp’s angle was 38.8° ± 3.5° in males and 40.7° ± 3.5° in females, with 97.5 percentiles of 46° and 47°, respectively. The CE angle was 32.1° ± 6.1° in males and 31.0° ± 6.1° in females, with 2.5 percentiles of 21° and 20°, respectively. The FHEI was 86.0 % ± 6.3 % in males and 85.6 % ± 6.6 % in females, with 2.5 percentiles of 74° and 73°, respectively. Conclusions Updated gender-specific reference ranges for radiographic measurements commonly used for hip dysplasia at skeletal maturity are reported, similar to or slightly wider than those described in the literature. Statistically significant gender differences have been confirmed for most of the measurements.